Modulating pipe-soil interface friction to influence HPHT offshore pipeline buckling. (15th December 2022) - de Leeuw, Lawrence W.; Diambra, Andrea; Kwon, Oh-Sung; Sextos, Anastasios
Abstract: High-Pressure High-Temperature offshore pipelines laid on the seafloor are subject to large temperature and pressure variations which manifest as axial pipeline loading. Pipes become unstable in this condition and buckles form to relieve the axial stress. Considerable theoretical and experimental energy has been directed at establishing controlling mechanisms and parameters to predict buckling and design pipeline systems to be resilient and serviceable. The pipe-soil interface friction plays a pivotal role in the rate of build-up of axial loads and in controlling the critical buckling threshold. Pipes adopting smooth polymer coatings have very low friction coefficients but experimental work has shown that simple roughening techniques make greater friction coefficients available to a designer. Presented are a series of numerical analyses carried out using Abaqus to model a pipeline resting on the seabed subject to typical HPHT pipeline conditions. Global stability response is assessed with pipe-soil friction coefficients varying from 0.25 to 0.75 and differential friction regimes are adopted. It is shown that targeted application of pipe sections with greater interface friction may be a useful design tool for manipulating global buckling phenomena and could be a useful additional tool for influencing the spacing in Virtual Anchor Spacing analysis. Highlights: Modulating pipe-soil interface friction influences distribution of global buckling. Modulating pipe-soil interface friction influences the magnitude of pipe buckles. Pipe end expansion is influenced by enhancing sections with greater friction. Engineers may use axial friction modulation to control Virtual Anchor Spacing.